Analysis of Brand Loyalty at Starbucks - Agarwal, Varsha (International Journal of Scientific Development and Research, 2022)
Brand loyalty is when a consumer prefers to buy the same brand of goods rather than competing brands. The bottom line benefits from brand loyalty since it can boost sales volume by keeping customers loyal to the brand and enabling premium pricing. In other words, when consumers discover the value of a brand, they 1) start making recurring purchases and 2) become price agnostic. From a business standpoint, enhancing brand loyalty leads to continued earnings because of long-term repeat consumers, a reduction in the need for marketing to expand the clientele, and premium pricing. In the coffee shop industry, Starbucks is renowned for having a significantly greater level of customer loyalty. The goal of this investigation is to determine how Starbucks was created.
ISME
Keywords: attitudinal loyalty; behavioral loyalty; brand loyalty; consumer behavior; loyalty marketing; Starbucks